Archaea Dominate the Ammonia-Oxidizing Community in Deep-Sea Sediments of the Eastern Indian Ocean—from the Equator to the Bay of Bengal - Wang, Jing; Kan, Jinjun; Zhang, Xiaodong; Xia, Zhiqiang; Zhang, Xuecheng; Qian, Gang; Miao, Yanyi; Leng, Xiaoyun; Sun, Jun (Frontiers in Microbiology, 2017)
Ammonia-oxidizing Archaea (AOA) and ammonia-oxidizing Bacteria (AOB) oxidize ammonia to nitrite, and therefore play essential roles in nitrification and global nitrogen cycling. To better understand the population structure and the distribution of AOA and AOB in the deep Eastern Indian Ocean (EIO), nine surface sediment samples (>3,300 m depth) were collected during the inter-monsoon Spring 2013. One sediment sample from the South China Sea (SCS) (2,510 m) was also included for comparison. The community composition, species richness, and diversity were characterized by clone libraries (total 1238 clones), and higher diversity of archaeal amoA genes than bacterial amoA genes was observed in all analyzed samples. Real time qPCR analysis also demonstrated higher abundances (gene copy numbers) of archaeal amoA genes than bacterial amoA genes, and the ratios of AOA/AOB ranged from 1.42 to 8.49 among sites. In addition, unique and distinct clades were found in both reconstructed AOA and AOB phylogeny, suggesting the presence of niche-specific ammonia-oxidizing microorganisms in the EIO. The distribution pattern of both archaeal and bacterial amoA genes revealed by NMDS (nonmetric multidimensional scaling) showed a distinct geographic separation of the sample from the SCS and most of the samples from the EIO following nitrogen gradients. Higher abundance and diversity of archaeal amoA genes indicated that AOA may play a more important role than AOB in the deep Indian Ocean. Environmental parameters shaping the distribution pattern of AOA were different from that of AOB, indicating distinct metabolic characteristics and/or adaptation mechanisms between AOA and AOB in the EIO, especially in deep-sea environments.